Specific features of cash flow formation and analysis in the process of evaluation of investment projects’ efficiency - Mackevičius, Jonas; Tomaševič, Vladuslav (Publishing House of the Wrocław University of Economics, 2009)
Investments play an increasingly important role in the current dynamic and competitive business environment. Well-planned and sound investments have a great effect on the financial position, ability to continue to make a profit, development and competitiveness of a company and contribute to the overall growth of the national economy. The efficiency of investments largely depends upon the evaluation of an investment project forecasting the economic and social benefits of the investments. An inaccurate evaluation of an investment project may lead to distortions of the results of investment activities as they will differ from the targets. As a result of this the efficiency of investments may be reduced or they may become loss-making. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 294-304